Analisis Efisiensi Thermal dan Konsumsi Bahan Bakar pada Burner Kompor SNI Sebagai Dasar Acuan Perencanaan Burner Mesin Stirling - Rahmadsyah Lubis; Jufrizal Jufrizal; Supriatno Supriatno; Nurdiana Nurdiana (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
This study aims to evaluate the performance of an LPG stove burner by assessing the flame temperature, fuel consumption, burner power, and thermal efficiency. The method employed is an experimental approach using a water boiling technique. The test materials used include 3 kg of LPG gas and water. The equipment utilized includes an SNI-compliant cooking stove, a pot, a digital scale, a rotameter flow meter, a gas regulator and hose, a stopwatch, a UT320D thermometer controller, an NPT stainless steel thermometer, and thermocouple sensor cables. The results show that during the first test with the stove set to the minimum setting, the average flame temperature at the burner reached 559.005 °C, with a maximum value of 589.2 °C. In the second test, with the stove set to the maximum setting, the average flame temperature reached 714.78 °C, with a maximum value of 769.3 °C. Fuel consumption was recorded at 0.391 kg in the first test and 0.545 kg in the second test. The burner power output was 1.754 kW in the first test and 2.225 kW in the second test. The thermal efficiency of the burner was recorded at 50.07% in the first test, increasing to 52.85% in the second test. The measurement and analysis of thermal efficiency and fuel consumption in this study can serve as a crucial guide in designing and developing burners for Stirling engines.